Wymiary tożsamości a ich podmiotowe i kontekstowe korelaty - Brzezińska, Anna Izabela; Piotrowski, Konrad; Garbarek-Sawicka, Elżbieta; Karowska, Kamila; Muszyńska, Kinga (My University, 2010)
The paper presents the results of two studies in which adolescents, emerging-adults and early-adults participated. The first study aimed to discover correlations between identity dimensions (exploration in breadth, exploration in depth, ruminative exploration, commitment making and identification with commitment) on the one hand, and temperament and gender on the other. Highly reactive and strongly persevering persons scored higher on three exploration scales than persons with low scores on these temperamental dimensions. High activity and low reactivity proved to be the most favourable configuration of temperamental dimensions for making commitments and identifying with them. The other study focused on correlations between anxiety level and personal financial situation. Here, a high anxiety level proved to be rather strongly connected to high ruminative exploration, while at the same time making it difficult for the person to make commitments and identify with them. Also, the income level and ability to satisfy their needs was shown to be linked both to the participants’ anxiety level and identity dimensions.
Subject variables and context variables in identity formation
W artykule zaprezentowano wyniki dwóch badań, w których udział wzięły osoby w okresie dorastania, wyłaniającej się dorosłości i wczesnej dorosłości. W pierwszym badaniu poszukiwano związków pomiędzy wymiarami tożsamości (eksploracją wszerz, eksploracją w głąb, eksploracją ruminacyjną, podejmowaniem zobowiązania, identyfikacją z zobowiązaniem) a temperamentem i płcią. Osoby wysoko reaktywne i silnie persewerujące osiągnęły wyższe wyniki w zakresie trzech skal eksploracji niż osoby uzyskujące niskie wyniki na tych wymiarach temperamentu. Wysoka aktywność i niska reaktywność to konfiguracja wymiarów temperamentu, która w największym stopniu sprzyja podejmowaniu zobowiązań i identyfikacji z nimi. W badaniu drugim skoncentrowano się na związkach wymiarów tożsamości z poziomem lęku i poczuciem bezpieczeństwa finansowego osób badanych. Wysoki poziom lęku dość silnie wiązał się z wysoką eksploracją ruminacyjną, jednocześnie utrudniając podejmowanie zobowiązań i identyfikację z nimi. Także poziom dochodów oraz możliwość zaspokajania potrzeb okazały się istotnie związane zarówno z poziomem lęku, jak i z wymiarami tożsamości.